Vinylogous Blaise Reaction: Conceptually New Synthesis of Pyridin-2-ones - Rao, H. Surya Prakash; Muthanna, Nandurka; Padder, Ashiq Hussain (Synlett, 2018)
A conceptually new synthesis of pyridine rings by a [C4 + CN] assembly has been developed by applying a vinylogous version of the classic Blaise reaction. The zinc-mediated reaction of (het)aryl or alkyl nitriles with ethyl-4-bromocrotonate provided a variety of C(6)-substituted pyridin-2-ones in a single-step.
Keywords: vinylogous Blaise reaction; pyridinones; pyridine ring synthesis; zinc catalysis; bromoalkenoates